(untitled) (Al-Academy, 2023)
This study deals with the subject of art criticism by using Erwin Panofsky’s theory to analyze a few Saudi artists’ works. The study aims to identify Panofsky’s theory and provide criticism of some Saudi artworks using it. The importance of the study is that it enriches the field of art criticism in the Kingdom of Saudi Arabia and helps critics and artists in using Panofsky’s theory to analyze artworks. The study sample consists of six artworks produced in 2021 by six contemporary Saudi artists. In the theoretical section, the study dealt with several topics; first, is art criticism, the second part presents Panofsky’s theory with its three stages, the final part deals with the beginning of Saudi art until present time and its sources of inspiration. The study at first, used a descriptive approach to describe the artworks and forming the theoretical framework. Then the analytical approach for applying the theory in the analysis of artistic works. The study concluded that Art Criticism is a very essential elements in influencing Fine Arts. Also, it helps artists to improve their methods. As for recommendations, it illustrates the need for updating art education curriculum, in addition to adding lessons in Art Criticism